DAMPAK KEGAGALAN PANEN TERHADAP KETAHANAN PANGAN RUMAH TANGGA TANI PADI DI KABUPATEN BANYUMAS - Rifki Andi Novia; Lutfi Zulkifli (Jurnal Agrisep)
This study aims to determine the impact of crop failure due to drought on household food security of rice farmers in Banyumas Regency which occurred during the second planting season in 2019. Analytical descriptive method was used in this study, with the technical implementation of the research using the survey method. The method of research analysis is by comparing the level of household food security of rice farmers in Banyumas Regency when farmers experience a normal harvest with when farmers experience harvest failure. Measurement of the level of food security using the Jonsson and Toole Model, namely by cross-classifying the Food Expenditure Share (FES) and Energy Adequacy Rate (EAR). After collecting and analyzing the data, it was found that crop failure did not affect the amount of energy adequacy ratio relative to farm households. However, crop failure affects the Share of Food Expenditure, where farming households that have high FES are increasing. With the increase in FES, this results in lower household food security, because FES and food security are inversely related. With the harvest failure, the number of farm households that are food resistant decreases, food vulnerability increases, food insecurity increases and food insecurity increases.